Applying Of Mindfulness-Based Stress Reduction (MBSR) Method To Reduce Anxiety Level In Pregnant Women With Gestational Hypertension: A Randomized Control Trial - Mestika Rija Helti Tanjung; Nilahayati, Nilahayati (Sean Institute, 2024)
This study aims to test the effectiveness of the Mindfulness-Based Stress Reduction (MBSR) method in reducing anxiety levels in pregnant women with gestational hypertension. The method used is a randomized control trial with 30 respondents divided into two groups: an intervention group that received MBSR for eight weeks and a control group that did not receive any intervention. The results show that the intervention group experienced a significant decrease in anxiety levels compared to the control group. The urgency of the research lies in the fact that gestational hypertension can increase the risk of complications during pregnancy and childbirth. Furthermore, the anxiety experienced by pregnant women can exacerbate the condition of gestational hypertension. Therefore, research on non-pharmacological methods that can reduce anxiety in pregnant women with gestational hypertension is crucial for improving the health quality of mothers and babies. The objective of this study is to test the effectiveness of the MBSR method in reducing anxiety levels in pregnant women with gestational hypertension. This study uses a randomized control trial method to test the effectiveness of the Mindfulness-Based Stress Reduction (MBSR) method in reducing anxiety levels in pregnant women with gestational hypertension. The respondents in this study were divided into two groups: an intervention group and a control group.